Draft Seventh Five Year Plan 1985-90 and Annual Plan 1985-86 Government of Gujarat - Planning Commission (Planning Commission, 1985)
Gujarat has witnessed remarkable progress in the last twenty four years of development sine it emerged as a separate State on 1st May, I960 This chapter outlines the profile of development during this period. The Third Five Year Plan (1931-56 ) was the first determined effort to initiate development in different regions of the State in a systematic way.
Government of Gujarat, Planning Division, General Administration Department